2021
DOI: 10.1098/rsif.2021.0532
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics modelling of photon, mass and heat transfer in coral microenvironments

Abstract: Coral reefs are constructed by calcifying coral animals that engage in a symbiosis with dinoflagellate microalgae harboured in their tissue. The symbiosis takes place in the presence of steep and dynamic gradients of light, temperature and chemical species that are affected by the structural and optical properties of the coral and their interaction with incident irradiance and water flow. Microenvironmental analyses have enabled quantification of such gradients and bulk coral tissue and skeleton optical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 78 publications
(154 reference statements)
0
18
0
Order By: Relevance
“…The effects of GFP-like proteins on the light environment experienced by coral symbionts are not simply dependent on the spectral properties of the isolated protein; rather, they are a product of the environmental and physiological regulation of the protein within its three-dimensional optical context. For example, microsensor measurements and optical modelling have shown that scattering by GFP-like proteins can enhance light penetration at low GFP concentrations, while high concentrations of GFP increase backscattering and reduce light penetration through the coral tissue ( Lyndby et al, 2016 ; Taylor Parkins et al, 2021 ). Variability in the distribution and arrangement of these proteins – diffuse or granular and ectodermal or endodermal – also affects how they interact with light ( Salih et al, 2000 ; Wangpraseurt et al, 2019 ), further indicating that spectrally similar GFP-like proteins can be involved in different light modulation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of GFP-like proteins on the light environment experienced by coral symbionts are not simply dependent on the spectral properties of the isolated protein; rather, they are a product of the environmental and physiological regulation of the protein within its three-dimensional optical context. For example, microsensor measurements and optical modelling have shown that scattering by GFP-like proteins can enhance light penetration at low GFP concentrations, while high concentrations of GFP increase backscattering and reduce light penetration through the coral tissue ( Lyndby et al, 2016 ; Taylor Parkins et al, 2021 ). Variability in the distribution and arrangement of these proteins – diffuse or granular and ectodermal or endodermal – also affects how they interact with light ( Salih et al, 2000 ; Wangpraseurt et al, 2019 ), further indicating that spectrally similar GFP-like proteins can be involved in different light modulation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Such information is also important for the development of models that simulate radiative transfer e.g. in corals (e.g., Taylor Parkins et al, 2021). While the function of the white granules in Cassiopea remains unknown, other pigments in Cassiopea have been speculated to be either photoprotective or photo-enhancing (Blanquet and Phelan, 1987; Phelan et al, 2006), similar to host pigments found in corals (e.g., Lyndby et al, 2016; Salih et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Pinpointing the triggers and outcomes of metal exchanges between corals and Symbiodiniaceae will allow a greater understanding of intricate aspects of their functional physiology and metabolic compatibility. While the elevated metal contents in the dinoflagellates relative to the host coral have been attributed to the metal demands of photo- Taylor Parkins et al, 2021), metallomes (Esslemont, Harriott & McConchie, 2000), and other aspects of their physiology including toxin production, oxygen production, symbiont densities, and transcriptomic activities (Drake et al, 2021), is anticipated to modulate metal exchanges between a coral and its dinoflagellate symbionts. Since acidic environments can enhance metal ion binding (Crist et al, 1981), metal transfer from host to dinoflagellate is likely promoted by the acidic nature of the symbiosome (pH 4), which in addition to stimulating photosynthesis (Barott et al, 2015) enhances metal ion binding and nutrient uptake (Rands, Loughman & Douglas, 1993).…”
Section: (D) Metal Requirements For Calcificationmentioning
confidence: 99%
“…While the elevated metal contents in the dinoflagellates relative to the host coral have been attributed to the metal demands of photosynthesis (Reichelt‐Brushett & Harrison, 2000; Metian et al ., 2015; Grima et al ., 2022), little is known about coral–Symbiodiniaceae metal exchanges. Widespread within‐colony variation of microenvironment (Kühl et al ., 1995; Taylor Parkins et al ., 2021), metallomes (Esslemont, Harriott & McConchie, 2000), and other aspects of their physiology including toxin production, oxygen production, symbiont densities, and transcriptomic activities (Drake et al ., 2021), is anticipated to modulate metal exchanges between a coral and its dinoflagellate symbionts. Since acidic environments can enhance metal ion binding (Crist et al ., 1981), metal transfer from host to dinoflagellate is likely promoted by the acidic nature of the symbiosome (pH ~4), which in addition to stimulating photosynthesis (Barott et al ., 2015) enhances metal ion binding and nutrient uptake (Rands, Loughman & Douglas, 1993).…”
Section: Metal Demand Transport and Exchangesmentioning
confidence: 99%